Etika Profesi Pemimpin dan Gaya Kepemimpinan di SDN 15 Baringin - Ramadani, Degita Laila; Jamilus, Jamilus (Journal of Islamic Education Leadership, 2023)
Professional Ethics of Leaders and Leadership Styles at SDN 15 Baringin.This article discusses the ethics of a leader in upholding justice and his leadership style towards specific communities and institutions. In every educational institution or company, a leader is needed. A good leader can provide trustworthy directions to his subordinates regarding the duties and responsibilities of a leader. Unsurprisingly, a leader requires ethics in carrying out responsible duties and functions. A quality leader can provide good direction and assignments for his subordinates. A leadership style triggers the nature of the leader. This style includes the types of leaders carrying out their duties and responsibilities. The urgency of a leader's leadership style will affect his performance in giving direction. In every institution and company, a leader holds the duties and responsibilities for the institutions he carries out. A leader has a high sense of authority to build his performance and quality